PENGELOLAAN ARSIP DATA SISWA MELALUI TATA USAHA DI SMKN 1 NGAWI: PENGELOLAAN ARSIP DATA SISWA - kamsini, imam ali mushthofa; Zuhriana Widya Rahayuningtyas; Abdul Aziz, Hanafi (Institut Agama Islam Ngawi, 2025)
In the era of rapidly developing information, archive management has become important for organizations, including educational institutions. This research aims to determine the practice of managing document archives at SMKS PGRI 1 Ngawi, East Java. This research uses qualitative descriptive techniques to analyze the records management process, related challenges, and their impact on management efficiency. Data collection was carried out by observing letters sent and received, diploma archives, and the student archive management process. The findings show that although SMKS PGRI 1 Ngawi has implemented recording procedures, there are still challenges such as a lack of understanding of staff and an integrated system. This study provides recommendations for improving the archives management system to support transparency and accountability in information management. It is hoped that the results of this research can become a reference for other educational institutions to improve their data management practices. Keywords: Administration, Records Management And Educational Institution